1997
DOI: 10.1016/s0014-2999(96)00957-0
|View full text |Cite
|
Sign up to set email alerts
|

Rhodamine 123 accumulates extensively in the isolated perfused rat kidney and is secreted by the organic cation system

Abstract: Rhodamine 123 has been shown to be a substrate for P-glycoprotein in multidrug resistant cells, In the present investigation the disposition of rhodamine 123 was studied in the isolated perfused rat kidney, After exposing the kidneys to perfusate concentrations ranging from 10 to 1000 n g/m l, the renal clearance was 4-1 times the clearance by glomerular filtration, respectively, indicating active and saturable secretion of rhodamine 123. The rate-limiting step in secretion was found to be membrane passage fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
38
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 26 publications
1
38
0
Order By: Relevance
“…did not decrease the P app B-A -to-P app A-B ratio to around 1.00. Our current data are not sufficient to provide a firm explanation of this phenomenon, but we speculate that it might be caused by the participation of other transporters in rhodamine123 transport since rhodamine123 has been reported to be also the substrate of other transporters such as OCTs (Masereeuw et al, 1997;van der Sandt et al, 2000).…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…did not decrease the P app B-A -to-P app A-B ratio to around 1.00. Our current data are not sufficient to provide a firm explanation of this phenomenon, but we speculate that it might be caused by the participation of other transporters in rhodamine123 transport since rhodamine123 has been reported to be also the substrate of other transporters such as OCTs (Masereeuw et al, 1997;van der Sandt et al, 2000).…”
Section: Discussionmentioning
confidence: 63%
“…However, it should be noted that, in addition to P-glycoprotein, other transporters (e.g. mutant BCRP and OCTs) have also been reported to transport rhodamine123 across the cellular membrane (Alqawi et al, 2004;Masereeuw et al, 1997;van der Sandt et al, 2000). van der Sandt and coworkers (2000) reported that rhodamine123, but not doxorubicin, could be transported by OCTs expressed in LLC-PK1 cells.…”
Section: Discussionmentioning
confidence: 99%
“…To confirm this speculation, the pharmacokinetics of Rho123 across the dually perfused rat placenta in situ was investigated. Rhodamine 123, a fluorescent dye, is a well established model compound for the evaluation of the transport activity of P-gp in different sites of the body and for testing of tumor cells for MDR mediated by P-gp (Ludescher et al, 1992;Masereeuw et al, 1997;de Lange et al, 1998;Yumoto et al, 1999;van der Sandt et al, 2000). Nevertheless, some authors suggest that a rOCT could also participate in Rho123 transport (Masereeuw et al, 1997;van der Sandt et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Rhodamine 123, a fluorescent dye, is a well established model compound for the evaluation of the transport activity of P-gp in different sites of the body and for testing of tumor cells for MDR mediated by P-gp (Ludescher et al, 1992;Masereeuw et al, 1997;de Lange et al, 1998;Yumoto et al, 1999;van der Sandt et al, 2000). Nevertheless, some authors suggest that a rOCT could also participate in Rho123 transport (Masereeuw et al, 1997;van der Sandt et al, 2000). To assess the permeability of the intact placental barrier for Rho123, transplacental passage of Rho123 across the placenta was expressed as the transplacental clearance per the wet weight of the placenta (milliliters per minute per gram).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation